Parallel overexpression and clinical significance of kallikrein-related peptidases 7 and 14 (KLK7 & KLK14) in colon cancer - Devetzi, Marina; Trangas, Theoni; Scorilas, Andreas; Xynopoulos, Dimitris; Talieri, Maroulio (Thrombosis and Haemostasis, 2013)
Currently available colon cancer (CC) markers lack sensitivity and specificity. Kallikrein-related peptidases (KLKs) present a new class of biomarkers under investigation for diverse diseases, including cancer. KLKs are co-expressed in various tissues participating in proteolytic cascades. KLK7 in human tumours facilitates metastasis by degrading components of the extracellular matrix. KLK14 promotes tumourigenesis by activating proteinase-activated receptors. In the present study we examined the concomitant expression of KLK7 and KLK14 in 245 colonic tissue specimens from 175 patients; 70 were pairs of cancerous-normal tissues, 31 were cancerous tissues and 74 were colonic adenomas. We used quantitative real-time PCR and proved that both genes are up-regulated in CC at the mRNA level. Receiver-operating characteristic (ROC) analysis of our results showed that both genes have discriminatory value between CC and adenoma tissues, with KLK14 obtaining greater distinguishing power (area under the curve [AUC]=0.708 for KLK14; AUC=0.669 for KLK7). Current work showed that the two genes are fairly co-expressed in all three types of colon tissues examined (normal rs=0.667, p<0.001, adenomas rs=0.373, p=0.001, carcinomas rs=0.478, p<0.001). KLK14 is associated with shorter disease-free survival (DFS) and overall survival (OS) of patients (p=0.003, p=0.016 respectively), whereas KLK7 only with shorter DFS (p=0.004). KLK7 and KLK14 gene expression can be regarded as markers of poor prognosis for CC patients with discriminating power between CC and adenoma patients.
Keywords: KLK7; KLK14; co-expression; colon cancer; cell lines